Is a global recession imminent? - Justin Damien Guénette; M. Ayhan Kose; Naotaka Sugawara (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
Global growth prospects have deteriorated significantly since the beginning of the year, raising the specter of global recession. This paper relies on insights gleaned from previous global recessions to analyze the recent evolution of economic activity and policies and presents plausible scenarios for the global economy in 2022-24. We report three major findings. First, every global recession since 1970 was preceded by a significant weakening of global growth in the previous year, as has happened recently. Second, the global economy is in the midst of one of the most internationally synchronous episodes of monetary and fiscal policy tightening of the past five decades. The policy actions in many countries are necessary to contain inflationary pressures, but their mutually compounding effects could have larger impacts than envisioned - both in tightening financial conditions and in steepening the global growth slowdown. Third, if the degree of global monetary policy tightening markets now expect is not enough to reduce inflation to targets, experience from previous global recessions suggests that the additional tightening needed could cause significant financial stress and increase the likelihood of a global recession next year. These findings imply that policymakers need to carefully calibrate, clearly communicate, and credibly implement their policy actions while considering potential international spillovers, especially given the globally synchronous withdrawal of monetary and fiscal policies. They also need to pursue supply-side measures to overcome constraints confronting labor markets, energy markets, and trade networks.
Keywords: E17; E32; E37; E58; F44; G01; 330; Global economy; growth scenarios; monetary policy; fiscal policy; global inflation; synchronization of policies